2021
DOI: 10.7717/peerj.11631
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mannan oligosaccharides on growth performance, nutrient digestibility, ruminal fermentation and hematological parameters in sheep

Abstract: Background Mannan oligosaccharides (MOS) are a promising feed additive in animal husbandry due to mainly improving animal health status. The purpose of this study was to investigate the effects of MOS on growth performance, nutrient digestibility, ruminal fermentation, and twelve hematological parameters in sheep. Methods Ninety-six healthy Hu rams with similar body weights were chosen and divided into four treatment groups (twenty-four rams in each group), in which four different doses of MOS were tested: 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 40 publications
(53 reference statements)
1
9
0
Order By: Relevance
“…Previous studies have shown that AO and its culture have different effects on serum biochemical indices such as phosphorus, urea nitrogen, and alkaline phosphatase activity ( 36 , 37 ), while the effect on blood cell composition has not been studied. The effects of nutritional additives on hematological parameters in sheep ( 13 ) and Nile tilapia ( 38 ) were usually insignificant, which were consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previous studies have shown that AO and its culture have different effects on serum biochemical indices such as phosphorus, urea nitrogen, and alkaline phosphatase activity ( 36 , 37 ), while the effect on blood cell composition has not been studied. The effects of nutritional additives on hematological parameters in sheep ( 13 ) and Nile tilapia ( 38 ) were usually insignificant, which were consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Hematological parameters such as blood cell content are typically auxiliary indexes used to monitor health conditions or metabolic processes of animals ( 13 ). The blood cell analysis results of the sheep in the present study showed that all indicators were within the normal reference range ( 35 ), and AOC supplementation did not affect the blood cell composition, indicating that the experimental sheep remained healthy and free from disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, dietary supplementation MOS did not affect the WBC count, EOS or BAS of dairy cows (35). Zheng et al (36) reported that MOS did not significantly influence basal hematological parameters because their effects on the animal body are slight. In the current study, dietary supplementation of GMOS significantly increased routine blood indicators like MON, PCT, PLT and PDW.…”
Section: Discussionmentioning
confidence: 95%
“…In livestock breeding, health-related traits are becoming a priority, while hematologic parameters are important to evaluate the health condition, feeding management and nutrition level of animal, and the variation hematologic traits are caused by genetic and non-genetic (e.g., breed, age, sex and management systems) (24). At present, the studies on sheep hematologic parameters mainly focus on nutrition level and breed (25)(26)(27). In this study, the hematologic traits were measured for 819 male Hu sheep aged 6 months under the same nutritional level and management conditions, and the descriptive statistics and heritability estimates were performed for these traits, the results shown the average values were within the reference ranges of sheep according to the previous studies (26), the coefficient of variation were >10%, suggesting that these indexes have a certain selection space in the Hu sheep population.…”
Section: Discussionmentioning
confidence: 99%